PENGARUH HEDONIST LIFESTYLE DAN SELF-ESTEEM TERHADAP PERILAKU KEUANGAN MAHASISWA UNIVERSITAS BENGKULU DENGAN GENDER SEBAGAI VARIABEL MODERASI - Puspakinasih, Rona (UNIB Press, 2024)
This study aims to examine the effect of a hedonist lifestyle and self-esteem on the financial behavior of Bengkulu University students with gender as a moderating variable. The research method used in this study is quantitative using primary data collected through questionnaires distributed online through various social media. This study has a total sample of 250 active students of the Diploma (D3) and Bachelor Degree (S1) programs at the University of Bengkulu. Data processing in this study used SPSS for Windows version 26. The results obtained from this study include, a hedonist lifestyle has a negative and significant effect on financial behavior, self-esteem has a positive and significant effect on financial behavior, gender is not able to moderate the effect of a hedonist lifestyle on financial behavior, gender is not able to moderate the effect of self-esteem on financial behavior, hedonist lifestyle, and gender simultaneously influence financial behavior. Keywords: Financial Behavior, Gender, Hedonist Lifestyle, Self-Esteem